The perceived brand image of imported Korean "small car" vehicles in the South African automotive market. - Razafinjoelina, Dimby (My University, 2016)
There are only few empirical studies that emphasise on consumer perception, and particularly on brand image, within the South African academic world of marketing. This is also the case for studies on Korean brand vehicles (Hyundai and Kia) and particularly studies on small car segment vehicles within the automotive academic research. However, with the continual increase of fuel price, the small car vehicle segment has invaded the South African and the world automotive market over the past decade; exponentially acquiring a massive and ascending volume of the market share. The above facts are the main reason why this study came to light, aiming to identify the brand images of both imported Korean brand (Hyundai and Kia) small car vehicles in the South African market. The study has been conducted on the ground of both of Keller’s studies (1993 and 2001) on Customer Based Brand Equity Pyramid model, where brand image consists of the four steps of the branding ladder (Brand salience, brand meaning, brand response and brand resonance) in building, conceptualising and measuring brand equity, characterised by the strength, importance and uniqueness of brand associations related to the brand reflected by the consumer’s perception. Consumers were asked about their brand perceptions regarding these three characteristics. The study was conducted within the Gauteng area only and the results will not be generalised to the overall population. Respondents were approached at shopping centres and car wash car parks. This study has focused on descriptive statistics analysis (DSA), assessing frequency distributions to derive its findings. With the acquired sample size, this study has concluded that, compared with other similar small car brands in SA, both brands are uniquely and strongly associated with reliability according to the group of consumers acquired in this study. However, the following results have also shown signs of being considered as valuable findings from the analysis but cannot be tagged as official ones due to iii the methodology and the sample size used during the study: - There are indications from the results that both brands tend to uniquely associated with reasonable market price and good fuel consumption compared to other similar brands. However, as indicated above, this result can only be confirmed with a larger sample size as the frequency distributions have been evenly spread across the dimensions. - As for Hyundai brand in particular, the study indicates that the brand is associated with mature and older people but this result once again requires a larger sample size. A key message retrieved from this study is that, despite the methodology and sample size used during the process, none of the findings have matched both brands’ current intended brand images and strategic positioning on the South African market. The researcher strongly believes that both companies (which partly belong to one another) could improve their local sales performances and increase their sales revenues if both brands’ managers and marketing officers revised their strategy in regards to consumers’ perception and the results obtained from this study.
MBA
Keywords: Automobile industry and trade -- South Africa.Brand choice -- South Africa. Consumer behavior -- South Africa.